Women in higher education: leadership, coordination, and bibliography - Hurtado-Reina, Jone; Meza, Paulina; Velasco, Erlantz (Frontiers in Education, 2024)
This study examines the role of women in the academic and scientific domain, emphasizing the need for institutions to ensure women's representation for an equitable system. By analyzing 794 syllabi from the Primary Education Degree within the Spanish University Network, we adopt a qualitative-comparative approach to assess women's involvement in the management and coordination of courses and their representation in the associated bibliographic materials. The findings reveal a predominantly androcentric environment where, despite women's participation in course leadership, their contributions to the bibliographic landscape are significantly limited. This research highlights the disparities in gender representation and calls for measures to enhance women's visibility in academic and scientific spaces.